Service delivery approaches related to hearing aids in low- and middle-income countries or resource-limited settings: A systematic scoping review. - Lauren K Dillard; Carolina M Der; Ariane Laplante-Lévesque; De Wet Swanepoel; Peter R Thorne; Bradley McPherson; Victor de Andrade; John Newall; Hubert D Ramos; Annette Kaspar; Carrie L Nieman; Jackie L Clark; et al. (PLOS Global Public Health)
Hearing loss is an important global public health issue which can be alleviated through treatment with hearing aids. However, most people who would benefit from hearing aids do not receive them, in part due to challenges in accessing hearing aids and related services, which are most salient in low- and middle-income countries (LMIC) and other resource-limited settings. Innovative approaches for hearing aid service delivery can overcome many of the challenges related to access, including that of limited human resources trained to provide ear and hearing care. The purpose of this systematic scoping review is to synthesize evidence on service delivery approaches for hearing aid provision in LMIC and resource-limited settings. We searched 3 databases (PubMed, Scopus, Ovid MEDLINE) for peer-reviewed articles from 2000 to 2022 that focused on service delivery approaches related to hearing aids in LMIC or resource-limited settings. Fifteen peer-reviewed articles were included, which described hospital-based (3 studies), large-scale donation program (1 studies), community-based (7 studies), and remote (telehealth; 4 studies) service delivery approaches. Key findings are that hearing aid services can be successfully delivered in hospital- and community-based settings, and remotely, and that both qualified hearing care providers and trained non-specialists can provide quality hearing aid services. Service delivery approaches focused on community-based and remote care, and task sharing among qualified hearing care providers and trained non-specialists can likely improve access to hearing aids worldwide, thereby reducing the burden of untreated hearing loss.